Secondary Immune Deficiency and Primary Immune Deficiency Crossovers: Hematological Malignancies and Autoimmune Diseases - Ballow, Mark; Sánchez-Ramón, Silvia; Walter, Jolan E. (Frontiers in Immunology, 2022)
Primary immunodeficiencies (PIDs), a heterogenous group of inborn errors of immunity, are predetermined at birth but may evolve with age, leading to a variable clinical and laboratory presentation. In contrast, secondary immunodeficiencies (SIDs) are acquired declines of immune cell counts and or/function. The most common type of SID is a decreased antibody level occurring as a consequence of extrinsic influences, such as an underlying condition or a side effect of some medications used to treat hematological malignancies and autoimmune disorders. Paradoxically, immune deficiencies initially attributed to secondary causes may partly be due to an underlying PID. Therefore, in the era of immune-modulating biologicals, distinguishing between primary and secondary antibody deficiencies (PAD and SAD) is of great importance. It can be difficult to unravel the relationship between PID, SID and hematological malignancy or autoimmunity in the clinical setting. This review explores SID and PID crossovers and discusses challenges to diagnosis and treatment strategies. The case of an immunodeficient patient with follicular lymphoma treated with rituximab illustrates how SID in the setting of hematological cancer can mask an underlying PID, and highlights the importance of screening such patients. The risk of hematological cancer is increased in PID: for example, lymphomas in PID may be driven by infections such as Epstein-Barr virus, and germline mutations associated with PID are enriched among patients with diffuse large B-cell lymphoma. Clues suggesting an increased risk of hematological malignancy in patients with common variable immune deficiency (CVID) are provided, as well as pointers for distinguishing PID versus SID in lymphoma patients. Two cases of patients with autoimmune disorders illustrate how an apparent rituximab-induced antibody deficiency can be connected to an underlying PID. We highlight that PID is increasingly recognized among patients with autoimmune cytopenias, and provide guidance on how to identify PID and distinguish it from SID in such patients. Overall, healthcare professionals encountering patients with malignancy and/or autoimmunity who have post-treatment complications of antibody deficiencies or other immune abnormalities need to be aware of the possibility of PID or SID and how to differentiate them.